Phenotypic characteristics and trypanosome prevalence of Mursi cattle breed in the Bodi and Mursi districts of South Omo Zone, southwest Ethiopia - Terefe, E.; Haile, Aynalem; Mulatu, W.; Dessie, Tadelle; Okeyo Mwai, Ally (Springer, 2015)
The study was conducted to characterize the morphological features of Mursi cattle breed and to identify the species of trypanosome infecting the cattle and its prevalence in these traditionally managed cattle in the Bodi and Mursi pastoral communities. Cattle body description and measurements were made on 201 matured animals. Blood samples were collected from 409 animals into heparin-treated capillary tubes and were centrifuged to 12,000 rpm for 5 min to identify trypanosome species from the wet smeared buffy coat and to estimate the degree of anemia (PCV). Tsetse flies were collected using phenol-treated biconical trap and the caught flies identified to species level. The breed possesses variable coat color pattern, coat color type, and have small to medium hump size on the thoracic vertebrae. Body measurement of Mursi cattle in the two locations did not show significant differences except chest girth, rump width, and horn length. Trypanosome prevalence in the Mursi cattle breed was 6.1 %. The highest trypanosome infection was caused byTrypanosoma congolense (56 %) followed by Trypanosoma vivax (40 %) and Trypanosoma brucei (4 %). Trypanosome prevalence significantly varies between dry (2.0 %) and late rainy (10.1 %) seasons (P < 0.001) and between lean (11.9 %) and medium (2.4 %) body condition score (P < 0.01). The PCV value was 22.1 ± 0.5 %, which is significantly varied with season (P < 0.01) and parasitism (P < 0.001). Parasitaemic cattle show the lowest PCV value (20.4 ± 1%) than aparasitaemic (23.7 ± 0.3 %) cattle and cattle with lean BCS showed the lowest (P < 0.0001) PCV value (20.4 ± 0.6 %). Tsetse fly species identified in the study area were Glossina pallidipes, Glossina morsitans submorsitans, and Glossina fuscipes. The number of flies captured in late rainy season was higher than in dry season (P < 0.01). Despite the existence of trypanosome and high tsetse fly infestation in the areas, large proportion of the Mursi cattle shows medium BCS, low trypanosome prevalence, and higher PCV value.